New formyl indole derivatives based on thiobarbituric acid and their nano-formulations; synthesis, characterization, parasitology and histopathology investigations - Walaa Ali Abdelhalim; Ahmed R. Rabee; Saied M. Soliman; Mohamed Hagar; Esraa A. Moneer; Basant A. Bakr; Assem Barakat; Matti Haukka; Hanaa A. Rasheed (Scientific Reports)
Abstract New formyl indole derivatives based on thiobarbituric acid were designed for targeting parasitological applications. The new compounds (5-((1H-indol-3-yl)methylene)-2-thioxodihydropyrimidine-4,6(1H,5H)-dione (3a), and 5-((1-benzyl-1H-indol-3-yl)methylene)-2-thioxodihydropyrimidine-4,6(1H,5H)-dione (3b) were synthesized as thioxodihydropyrimidine derivatives via aldol condensation reaction. The structures of the synthesized compounds were confirmed based on their spectral data via FT-IR, 1H and 13C NMR spectral characterization. In addition, the structure of 3a is confirmed using X-ray crystallography. The synthesized compounds were prepared in nm scale via chitosan as a matrix, and their size was measured via scanning electronic microscope. Interestingly, the newly synthesized nano formulations show higher positive zeta potential (mV) values + 29.6 and + 26.1 for compounds NP-3a, and NP-3b; respectively. These compounds were tested for their parasitological activity. The results revealed that 3b had a great activity against cryptosporidium infection. Moreover, the nano formulation of compound 3b showed a significant reduction percent of oocyst count of cryptosporidium infected mice representing 66%. Furthermore, these compounds were screened by in-vitro hemolytic activity assay (IC50) values (cytotoxicity on RBCs) to assess their cytotoxic potentials and safety profiles.